The role of UNESCO global geoparks in promoting geosciences education for sustainability - Catana, M. M. (2020)
Following the establishment in 2000 of the first geoparks, the role of UNESCO Global Geoparks (UGGps) in geoscience education for sustainability needs to be characterized and understood. This is particularly relevant because education is one of the three main pillars of UGGps. In fact, UNESCO Global Geoparks are excellent opportunities to assist schools as outdoor classrooms and to be incubators of sustainable development, sustainable lifestyles, the appreciation of natural and cultural diversity, and the promotion of peace. For these reasons, UGGps are also effective strategies for the promotion of the seventeen United Nations Sustainable Development Goals (Agenda 2030). The analysis of the data obtained with an online questionnaire answered by seventy-three UGGps from thirty-five countries around the world allowed the characterization of the role played by geoparks in the promotion of geosciences education for sustainability through educational programs specifically addressed to the school community. This characterization will support the establishment of proposals of new methods, strategies, and resources to encourage the development of new educational programs in UGGps.